Marketing match: how sociodemographics influence user acceptance of social marketing appeals in oral health promotion / Raja Nur Adilah Raja Abdul Rahman ... [et al.] - Raja Abdul Rahman, Raja Nur Adilah; Nik Mohd Rosdy, Nik Mohd Mazuan; Rosli, Hafizah; Md Sabri, Budi Aslinie (Faculty of Dentistry, 2025)
Objective: This study aimed to evaluate how sociodemographic factors influence user acceptance of different social marketing appeals. Materials and Methods: This study was designed as a three-armed randomised controlled trial, with the non-emotional (rational) appeal serving as the control group. We utilised an adapted, translated, and validated modified Technology Acceptance Model (TAM) questionnaire consisting of 23 items on a five-point Likert scale to assess user acceptance. Participants were randomly assigned to watch one of three intervention videos on oral cancer, each featuring a distinct appeal: rational (Video 1), humour (Video 2), and fear-based messaging (Video 3). Results: A total of 322 participants viewed videos featuring rational (34.0%), humour (33.0%), and fear (33.0%) appeals. Gender distribution was 51.2% male and 48.8% female, with age groups comprising 34.2% in early adulthood, 33.8% in middle adulthood, and 32.0% in the elderly. Educational levels were evenly split between high school or below and tertiary education or higher, each at 50.0%. Overall, participants exhibited positive acceptance across all demographics for the videos, with no significant differences in gender,